Thyroid function status and heterogeneity of efficacy of maintenance cognitive stimulation in late-life dementia: a stratified observational study of subclinical hypothyroidism/hyperthyroidism - Zhang, Ruili; Zhou, Yongling; Wang, Shan; Li, Feng; Zhao, Xuan; Jia, Bowen; Li, Xiaxia; Yang, Junhui; Yang, Ling; Yu, Haiyuan; Yu, Xiaomin; Xu, Xuebing (Frontiers in Neurology, 2026)
BackgroundCognitive stimulation therapy (CST) and its maintenance phase (MCST) can benefit dementia. We evaluated treatment–effect heterogeneity by euthyroid versus subclinical hypothyroidism/hyperthyroidism during the 16-week maintenance period following CST.MethodsWe conducted a prospective single-center cohort embedded in routine CST to MCST. All entrants to 7-week CST were assessed at baseline/8/16/24 weeks. Sixteen-week MCST occurred per usual care. Baseline TSH/FT4/FT3 are classified as euthyroid, subclinical hypothyroidism (SCH), or hyperthyroidism (SHyper). Co-primary outcomes were 24-week Montreal Cognitive Assessment (MoCA) and Zarit changes. We used doubly robust inverse-probability-of-treatment weighting combined with linear mixed-effects models to test MCST×thyroid interactions and controlled for multiple testing with a false-discovery-rate approach.ResultsOf a total of 242 participants screened, 200 were enrolled, and 174 (87.0%) completed the 24-week study session. MCST continuation was 112 of 200 (56.0%) participants. Thyroid status was available for 196 participants, with 137 (69.9%) being euthyroid, 45 (23.0%) being SCH, and 14 (7.1%) being SHyper. The MCST×thyroid interaction for 24-week MoCA change was −0.9 (95% CI −1.6 to −0.2; p = 0.012; q = 0.012); MCST improved MoCA by +1.4 (95% CI +0.6 to +2.2) in euthyroid versus +0.5 (−0.4 to +1.3) in subclinical dysfunction. For Zarit, the interaction was +2.1 (95% CI +0.5 to +3.7; p = 0.011; q = 0.012), with larger burden reduction in euthyroid (−3.4; 95% CI −5.3 to −1.5) than subclinical dysfunction (−1.3; −3.1 to +0.4). Secondary outcomes favored MCST but were attenuated at higher TSH levels (spline χ2 = 8.9; p = 0.030). Agitation occurred in 3 of 200 participants (1.5%).ConclusionMCST improved cognition and reduced caregiver burden over 24 weeks, with smaller benefits in subclinical thyroid dysfunction. Thyroid-aware personalization may better target maintenance cognitive interventions in late-life dementia.